Research Hotspots and Trends Analysis of TFEB: A Bibliometric and Scientometric Analysis - Zhou, Runjin; Lin, Xiaoling; Liu, Dongmin; Li, Zhao; Zeng, Jingchun; Lin, Xingdong; Liang, Xiaodi (Frontiers in Molecular Neuroscience, 2022)
Objective. To explore the development context, research hotspots and frontiers of Transcription factor EB (TFEB) from 1991 to 2021 by bibliometric analysis. Methods. Publications about TFEB research from 1991 to 2021 were retrieved from the Web of Science Core Collection (WoSCC). Excel 2007 was used to collect basic information, including publications, research areas. VOSviewer 1.6.17 was used to analyze co-authorship of countries, institutes and authors. Co-citation of cited authors， cited references were analyzed by CiteSpace V.5.8.R3. In addition, CiteSpace was used to analyze keywords cluster and forecast research frontiers. Results. A total of 1,059 literatures were retrieved, including 1,340 research institutes and 393 academic journals. The main area of research related to TFEB is biology (340), the most published country and institutes were the United States (487) and Baylor College of Medicine (70). Settembre C owned the highest co-citations (663). Trending keywords may indicate frontier topics, including “Alzheimer's disease”, “Parkinson disease”, “(p21; q12)”, “melanoma”, “pancreatic cancer”, “breast cancer”, “calcineurin”, “TFE3”, “trehalose” and “curcumin”. Conclusion. This research provides valuable information for the study of TFEB. Disease research focuses more on neurodegenerative diseases (NDs) and tumors. Trehalose and curcumin are novel agents acting on TFEB. Rap-TRPML1-Calcineurin-TFEB and TFE3 are increasing signal pathway researches, similarly, the molecular biological mechanism of TFEB needs further exploration.